Perspectives on the Importance and Usage of New Technologies in Accounting - Anna KARMAŃSKA; Maciej TUSZKIEWICZ (Communications of International Proceedings, 2021)
The aim of the article is to measure (1) knowledge and perspective of people to the importance of new technologies in accounting, (2) which technologies will be particularly useful in specific accounting areas (3) influence of COVID-19 pandemic on the pace of implementation and usage of new technologies in accounting. A survey questionnaire in Polish and English was carried out resulting in 269 responses. The findings indicate, that of proposed new technologies, cloud computing is the best known technology with a mean of 3.67, while robotization and automation will be the most important technology in accounting (4.27) and was the most frequent choice in specific accounting areas (4 out of 8) followed by artificial intelligence (3 areas). COVID-19 pandemic has accelerated the introduction of new technologies in accounting (3.59), encouraged companies to implement new technologies in accounting (3.86) and changed permanently the way in which companies work. The results add to existing knowledge by identifying which new technologies could become the driving factors in accounting in the following years. This knowledge will help company managers in deciding what type and in what form new technologies should be implemented to best serve employees and thus the enterprise.
Keywords: New Technologies in Accounting; Accounting; Accounting Information Systems.